Spin‐Orbit Torque in Van der Waals‐Layered Materials and Heterostructures - Wei Tang; Haoliang Liu; Zhe Li; Anlian Pan; Yu‐Jia Zeng (Advanced Science, 2021)
Abstract Spin‐orbit torque (SOT) opens an efficient and versatile avenue for the electrical manipulation of magnetization in spintronic devices. The enhancement of SOT efficiency and reduction of power consumption are key points for the implementation of high‐performance SOT devices, which strongly rely on the spin‐orbit coupling (SOC) strength and magnetic properties of ferromagnetic/non‐magnetic heterostructures. Recently, van der Waals‐layered materials have shown appealing properties for use in efficient SOT applications. On the one hand, transition‐metal dichalcogenides, topological insulators, and graphene‐based heterostructures possess appreciable SOC strength. This feature can efficiently converse the charge current into spin current and result in large SOT. On the other hand, the newly discovered layered magnetic materials provide ultra‐thin and gate‐tunable ferromagnetic candidates for high‐performance SOT devices. In this review, the latest advancements of SOT research in various layered materials are summarized. First, a brief introduction of SOT is given. Second, SOT studies of various layered materials and heterostructures are summarized. Subsequently, progresses on SOT‐induced magnetization switching are presented. Finally, current challenges and prospects for future development are suggested.